Craving Responses to Methamphetamine and Sexual Visual Cues in Individuals With Methamphetamine Use Disorder After Long-Term Drug Rehabilitation - Huang, Shucai; Zhang, Zhixue; Dai, Yuanyuan; Zhang, Changcun; Yang, Cheng; Fan, Lidan; Liu, Jun; Hao, Wei; Chen, Hongxian (Frontiers in Psychiatry, 2018)
Studies utilizing functional magnetic resonance imaging (fMRI) cue-reactivity paradigms have demonstrated that short-term abstinent or current methamphetamine (MA) users have increased brain activity in the ventral striatum, caudate nucleus and medial frontal cortex, when exposed to MA-related visual cues. However, patterns of brain activity following cue-reactivity in subjects with long-term MA abstinence, especially long-term compulsory drug rehabilitation, have not been well studied. To enrich knowledge in this field, functional brain imaging was conducted during a cue-reactivity paradigm task in 28 individuals with MA use disorder following long-term compulsory drug rehabilitation, and 27 healthy control subjects. The results showed that, when compared with controls, individuals with MA use disorder displayed elevated activity in the bilateral medial prefrontal cortex (mPFC) and right lateral posterior cingulate cortex in response to MA-related images. Additionally, the anterior cingulate region of mPFC activation during the MA-related cue-reactivity paradigm was positively correlated with craving alterations and previous frequency of drug use. No significant differences in brain activity in response to pornographic images were found between the two groups. Compared to MA cues, individuals with MA use disorder had increased activation in the occipital lobe when exposed to pornographic cues. In conclusion, the present study indicates that, even after long-term drug rehabilitation, individuals with MA use disorder have unique brain activity when exposed to MA-related cues. Additionally, our results illustrate that the libido brain response might be restored, and that sexual demand might be more robust than drug demand, in individuals with MA use disorder following long-term drug rehabilitation.